Stercoral Colitis Complicated with Ischemic Colitis in a Myotonic Dystrophy Patient: A Rare Case Report - Almayoof, Mustafa; Almarry, Hissa Hamad; Subahi, Eihab; Ajaj, Arwa; Alfitori, Gamal (Archives of Clinical and Medical Case Reports, 2022)
Stercoral Colitis (SC) is a rare and serious inflammatory condition of the large bowel wall occurs due to distention and increase in the intraluminal pressure secondary to impaction of hard stool. Ischemic colitis may complicate SC and may progress to perforation, and subsequently peritonitis and death if not recognized and treated urgently. Myotonic Dystrophy (DM) has been associated with disorders of the gastrointestinal tract and manifests as reflux, constipation, and dysphagia. Severe colonic impaction, colitis and intestinal pseudo-obstruction, are rarely reported with this condition in the literature. We describe a case of stercoral colitis in a (DM) patient that was successfully treated with conservative measures. We herein present 23-year-old male known case of Myotonic dystrophy (DM) with history of chronic constipation on laxatives, presented with 3 days of abdominal distention, pain, absolute constipation and occasional fecal vomiting. Abdominal exam showed distended abdomen with generalized tenderness with no rigidity or rebound- tenderness. Lab tests were significant for leukocytosis and lactic acidosis. CT (computed tomography) abdomen with contrast: showed marked distention of the rectosigmoid colon with impacted stool, bowel wall thickening and surrounding fat stranding without any finding suggestive of perforation. The patient was diagnosed as case of (SC) with ischemic colitis and treated conservatively with manual evacuation, enema, and laxatives. He dramatically improved and was discharged home. Our conclusion is that stercoral colitis can occur in young patients with a history of chronic constipation like in (DM) patients. Chronic constipation complicated by fecal impaction is the major risk factor for (SC). Computed tomography (CT) is the gold standard imaging modality for the diagnosis of (SC). Elevated lactic acid should raise the suspicion of ischemic colitis complicating the (SC) which requires urgent intervent